A common SNP in the CD40 region is associated with systemic lupus erythematosus and correlates with altered CD40 expression: implications for the pathogenesis. Issue 12 (12th September 2011) - Vazgiourakis, Vassilios M; Zervou, Maria I; Choulaki, Christianna; Bertsias, George; Melissourgaki, Maria; Yilmaz, Neslihan; Sidiropoulos, Prodromos; Plant, Darren; Trouw, Leendert A; Toes, Rene E; Kardassis, Dimitris; Yavuz, Sule; et al.
Abstract : Background: In systemic lupus erythematosus (SLE) sustained CD40L expression by T cells and platelets activates a variety of cells via its receptor CD40 contributing to disease pathogenesis. Although CD40 has recently been identified in genome-wide association study as a novel rheumatoid arthritis susceptibility gene such an association has not been documented for SLE. Objective: To investigate whether the rs4810485 CD40 single nucleotide polymorphism (SNP) is associated with increased risk for SLE and its impact on CD40 expression. Materials and methods: The primary sample set consisted of 351 patients with SLE and 670 matched healthy controls of Greek origin. 158 patients with SLE and 155 controls from Turkey were used as a replication sample. Genotyping of rs4810485 was performed by restriction fragment length polymorphism and the Sequenom MassArray technology. The expression of CD40 mRNA and protein was assessed in unstimulated and lipopolysaccharide-stimulated peripheral blood mononuclear cells by quantitative real time PCR and flow cytometry, respectively. Results: The minor allele T of CD40 rs4810485 SNP was significantly under-represented in Greek patients with SLE compared with healthy controls (OR=0.65, 95% CI 0.54 to 0.79). The association was replicated in the Turkish cohort (OR=0.57, 95% CI 0.41 to 0.80; meta-analysis of 509 patients with SLE and 825 healthy controls: OR=0.63, 95% CI 0.53 to 0.74, p = 2×10 −8 ). In both cases and controls, the rs4810485 G/T and T/T genotypes were associated with significantly reduced CD40 mRNA and protein expression in peripheral blood CD14+ monocytes and CD19+ B cells compared with G/G genotype, both under basal conditions and following stimulation. Conclusions: CD40 has been identified as a new susceptibility locus in Greek and Turkish patients with SLE. The rs4810485 minor allele T is under-represented in SLE and correlates with reduced CD40 expression in peripheral blood monocytes and B cells, with potential implications for the regulation of aberrant immune responses in the disease.